Biomimetic Oxidations Catalyzed by Transition Metal Complexes 2000
DOI: 10.1142/9781848160699_0003
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Oxygenations Related to Cytochrome P450: Metal-Oxo and Metal-Peroxo Intermediates

Abstract: Oxometalloporphyrin Intermediates in Enzymatic ProcessesMetalloenzymes catalyze a host of biological oxidation reactions that are crucial to life processes. The cytochromes P450, an important family of heme-iron metalloenzymes, are oxidoreductases that activate molecular oxygen (O2) and incorporate one of the oxygen atoms into a wide variety of biological substrates, with concurrent two-electron reduction of the other oxygen atom to H 2 0.' The structure, biochemistry, molecular biology and the chemistry of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 99 publications
1
70
0
Order By: Relevance
“…The principal features of the consensus mechanism of cytochrome P450 (19) are as outlined in Scheme 1: binding of substrate to the enzyme, sometimes accompanied by a spin-state change of the iron, to afford an enzyme-substrate adduct 3; reduction of the ferric cytochrome P450 by an associated reductase with an NADPH-derived electron to the ferrous cytochrome P450 4; binding of molecular oxygen to the ferrous heme to produce a ferrous cytochrome P450-dioxygen complex 5, similar to the situation in oxymyoglobin; a second one-electron reduction and protonation to arrive at the Fe(III)-hydroperoxy complex 6; protonation and heterolytic cleavage of the OOO bond in 6 with concurrent production of a water molecule to form a reactive iron-oxo intermediate 7; and, finally, oxygen atom transfer from this ironoxo complex 7 to the bound substrate to form the oxygenated product complex 8. Product dissociation completes the cycle.…”
Section: Oxygen Activation By Heme Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal features of the consensus mechanism of cytochrome P450 (19) are as outlined in Scheme 1: binding of substrate to the enzyme, sometimes accompanied by a spin-state change of the iron, to afford an enzyme-substrate adduct 3; reduction of the ferric cytochrome P450 by an associated reductase with an NADPH-derived electron to the ferrous cytochrome P450 4; binding of molecular oxygen to the ferrous heme to produce a ferrous cytochrome P450-dioxygen complex 5, similar to the situation in oxymyoglobin; a second one-electron reduction and protonation to arrive at the Fe(III)-hydroperoxy complex 6; protonation and heterolytic cleavage of the OOO bond in 6 with concurrent production of a water molecule to form a reactive iron-oxo intermediate 7; and, finally, oxygen atom transfer from this ironoxo complex 7 to the bound substrate to form the oxygenated product complex 8. Product dissociation completes the cycle.…”
Section: Oxygen Activation By Heme Proteinsmentioning
confidence: 99%
“…For substrates with a very strong COH bond and a small steric size, both effects would push the reaction coordinate toward a tighter radical cage. Indeed, it has been shown that the effective lifetime of a radical intermediate can even be affected by the stereochemistry of the hydrogen abstraction event (19). Here, the pro-R hydrogen of ethyl benzene was hydroxylated with nearly complete retention of configuration at carbon whereas the pro-S hydrogen underwent significant racemization.…”
Section: Mechanisms and Molecular Trajectories For Hydroxylation By Cmentioning
confidence: 99%
“…They are capable of catalyzing a wide range of oxidation reactions: from hydroxylation of alkanes and epoxidation of alkenes to drug oxidation and DNA cleavage. [1][2][3] More recently, porphyrins have attracted even more attention from researchers in various fields due to their phototherapeutic properties. [4][5][6] Photodynamic therapy (PDT) is a form of neoplastic diseases treatment using a photosensitizer, oxygen and light.…”
Section: Introductionmentioning
confidence: 99%
“…26 In this respect, initial assays in the oxidation of cyclohexane catalized by 1-SiN, 1-SiN(IPG) and 1-CPS gave very low yields of the products cyclohexanol and cyclohexanone ( III species in the oxidative processes. In addition, 1-SiN, 1-SiN(IPG) and 1-CPS showed to be efficient catalysts in the epoxidation of (Z)-cyclooctene by PhIO even after three successive recycling steps, making them promising catalysts for selective epoxidations.…”
Section: Epoxidation Of (Z)-cyclooctene With Phiomentioning
confidence: 99%